Customizable fabrication for auxetic graphene assembled macrofilms with high conductivity and flexibility. (June 2020) - Li, Peng; Wang, Zhe; Song, Rongguo; Qian, Wei; Wen, Pin; Yang, Zhugen; He, Daping
Abstract: Auxetic materials with negative Poisson's ratios unusually exhibit intuitive mechanical behaviors, such as cross-section expansion instead of contraction during tension. Such behaviors are interesting because they may enhance unusual mechanical properties. However, controllable preparation of materials with negative Poisson's ratio is still a major challenge. In this study, we report the synthesis of a flexible auxetic graphene assembled macrofilm (GAMF) from graphene oxide nanosheets by a thermal annealing and press assistant method. The obtained materials exhibit good flexibility and significantly wide tunable negative Poisson's ratios ranging from −0.11 to −0.53. We also develop a reconstruction model for characterization the uniaxial tension of GAMF based on X-ray tomographic images. The tensile simulation result predicts the function relationship between Poisson's ratio and critical thickness of pore channels, which is in good agreement with the experimental data. As a result, an effective tunable way is proposed for customizable fabrication of GAMF with tunable negative Poisson's ratios, and the GAMF materials with good flexibility, high electrical conductivity and superior auxetic behavior looks promising for future development of wearable electronics. Graphical abstract: Microporous structure was constructed as determining factor in auxetic performance of fabricated GAMF with high conductivity and outstanding flexibility through graphitization of treated graphene oxide precursor. The simulation results showed that critical thickness had an impact on NPR performance. GAMFs with different critical thicknesses were fabricated and Poisson's ratios ranging from −0.11 to −0.53 were recorded, which aligned well with the predictions and suggesting promising applications in flexible sensor devices and wearable electronic engineering. Image 1